Acoustic analysis of the phoneme "ch" in Chilean Spanish variety spoken in Santiago - Roman-Montes de Oca, D (PONTIFICIA UNIV CATOLICA CHILE, FAC LETRAS, 2025)
One of the most known sociophonetic variations in Chilean Spanish is the one referring to the voiceless affricate palatal phoneme /t integral/ and the sociolinguistic distribution of its allophones, with fricative prominence, related to speakers coming from lower sociocultural groups, and with occlusive prominence coming from the upper ones. The present study intends to establish which are the phonetic-phonological factors and social variables that determine the phoneme s pronunciation in the Chilean Spanish variety spoken in Santiago. In this context, the factors of syllable position, sex and sociocultural origin are the variables to be tested as the determinants ones. 30 middle aged men and women residents in Santiago and coming from three sociocultural groups (low, middle and upper) participated in a sociolinguistic semi-spontaneous interview. From the collected data, 956 word items, including the pronunciation of the phoneme, were selected for an acoustic analysis, in order to measure the occlusion and friction duration s moments, the zero crossing and the friction s center of gravity. The results show that the initial syllable position is a determinant factor in the pronunciation of the phoneme across all the three sociocultural groups, whereas the sex variable is significant according to the friction s center of gravity. In this context, it could be asserted that the friction moment is the most relevant one and that the pronunciation tends to be high-pitched at the beginning of the announced words, especiallythose pronounced bywomen. Therefore, it is being questioned whetherthis new data could predetermine the phoneme s perception and the linguistic bias concerning its use.